1989
DOI: 10.1002/1097-0142(19890601)63:11<2169::aid-cncr2820631117>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of epidermal growth factor receptor in esophageal squamous cell carcinomas

Abstract: The prognostic value of epidermal growth factor (EGF) receptor level was studied in 32 patients with esophageal squamous cell carcinoma. The EGF receptor levels of tumors were measured by iodine 125 (Iz5I)-EGF binding assay, and the patients subsequently were divided into two groups: a group with high EGF binding capacities (22.5% of input), and a group with low EGF binding capacities (<2.5% of input). The cumulative survival rates for the two groups were calculated by the Kaplan-Meier method. The generalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
2
7

Year Published

1991
1991
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(68 citation statements)
references
References 15 publications
2
57
2
7
Order By: Relevance
“…In particular, we and others have recently reported that the overexpression of EGFR of oesophageal SCC, partially accounted for by gene amplification, is found in 50 -70% (Itakura et al, 1994;Hanawa et al, 2006), and is indicative of a poor prognosis (Ozawa et al, 1989;Yano et al, 1991). Moreover, we showed that the overexpression of HER-2 in oesophageal SCC was found in 30.3% (Mimura et al, 2005b).…”
supporting
confidence: 67%
“…In particular, we and others have recently reported that the overexpression of EGFR of oesophageal SCC, partially accounted for by gene amplification, is found in 50 -70% (Itakura et al, 1994;Hanawa et al, 2006), and is indicative of a poor prognosis (Ozawa et al, 1989;Yano et al, 1991). Moreover, we showed that the overexpression of HER-2 in oesophageal SCC was found in 30.3% (Mimura et al, 2005b).…”
supporting
confidence: 67%
“…Secretion of TGF a/EGF and overexpression of EGF receptors were not only reported in human esophageal carcinoma cell lines, but were also detected in human esophageal carcinoma tissues (Lu et al, 1988;Ozawa et al, 1987Ozawa et al, , 1989. In fact, the prognosis is poorer in esophageal cancer patients whose tumors express a higher level of EGF receptors (Iihara et al, 1993;Ozawa et al, 1989). Thus, the mitogenic and anti-apoptotic signals transduced from EGF receptors may play a very important role in the growth and prognosis of human esophageal carcinomas.…”
Section: Discussionmentioning
confidence: 98%
“…This study and others have demonstrated that esophageal squamous cell carcinoma cells express higher levels of EGFR and HER2 compared with other types of malignant cells (18,20). In addition, a correlation between EGFR expression and prognosis of esophageal cancer has also been reported (19). Therefore, this may suggest that targeting therapies against EGFR and HER2 may be promising for esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In esophageal squamous cell carcinoma, there is frequent overexpression of EGFR and a correlation between EGFR expression and prognosis has also been reported (18,19). In addition, HER2 expression is detectable in a variety of esophageal tumors (20).…”
Section: Introductionmentioning
confidence: 99%